2019
DOI: 10.1080/22221751.2019.1693247
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics and interactions of respiratory pathogen carriage among French pilgrims during the 2018 Hajj

Abstract: We conducted this study to describe the dynamics of the acquisition of respiratory pathogens, their potential interactions and risk factors for possible lower respiratory tract infection symptoms (LRTI) among French pilgrims during the 2018 Hajj. Each participant underwent four successive systematic nasopharyngeal swabs before and during their stay in Saudi Arabia. Carriage of the main respiratory pathogens was assessed by PCR. 121 pilgrims were included and 93.4% reported respiratory symptoms during the study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 40 publications
0
54
0
Order By: Relevance
“…The epidemiology of respiratory viruses in KSA is likely affected by the gathering of more than 10 million Muslims in the holy sites of Makkah and Medina during the Umrah and Hajj seasons [ 11 ]. In pilgrims, human rhinovirus (HRV), common human coronaviruses (HCoV), and influenza virus were the respiratory viruses most frequently acquired at the Hajj [ 2 , 5 , 6 , 12 16 ].…”
Section: Transmission Of Respiratory Viruses During the Hajj And Umramentioning
confidence: 99%
See 3 more Smart Citations
“…The epidemiology of respiratory viruses in KSA is likely affected by the gathering of more than 10 million Muslims in the holy sites of Makkah and Medina during the Umrah and Hajj seasons [ 11 ]. In pilgrims, human rhinovirus (HRV), common human coronaviruses (HCoV), and influenza virus were the respiratory viruses most frequently acquired at the Hajj [ 2 , 5 , 6 , 12 16 ].…”
Section: Transmission Of Respiratory Viruses During the Hajj And Umramentioning
confidence: 99%
“…More recently (2014 to 2017), in a 4-year cohort of 485 French pilgrims, 26.9% participants acquired HRV after their pilgrimage [ 18 ]. The dynamic of HRV acquisition during the pilgrimage was recently described in French pilgrims [ 6 ]. The authors showed an early increase in HRV carriage during the first days of the pilgrimage with a prevalence 24 times higher than that of pre-travel samples.…”
Section: Transmission Of Respiratory Viruses During the Hajj And Umramentioning
confidence: 99%
See 2 more Smart Citations
“…URTI is the most common medical complication among Hajj pilgrims [12][13][14][15], and studies showed that the majority of URTIs are treated with antibacterial agents (henceforth referred to as antibiotics without specification) [16], even though up to 95% at onset of symptoms, during Hajj, are known to be viral [17]. A recent study revealed that around 93% of pilgrims develop respiratory symptoms, of which 78% of tested samples were positive for at least one pathogen [18]. The most commonly found bacterial causes for respiratory infections were Haemophilus influenzae and Staphylococcus aureus, and viral causes were human rhinoviruses [19][20][21].…”
Section: Introductionmentioning
confidence: 99%